Introductory medical-surgical nursing - Timby, Barbara Kuhn; Smith, Nancy E. (Nancy Ellen), 1949- (Philadelphia : Lippincott Williams and Wilkins, 2007)
Accompanying CD-ROM contains a bank of new NCLEX-style review questions for each chapter, a complete multimedia library including a set of dynamic animations of body processes, audio pronunciations of key terms, and a Spanish medical glossary. Also included are the answer keys for the book's Stop Think and Respond boxes and End of Unit Exercises
UNIT 1 Nursing Roles and Responsibilities UNIT 2 Psychosocial Aspects of Nursing UNIT 3 Caring for Clients With Common Psychosocial Problems UNIT 4 Caring for Clients With Common Medical-Surgical Problems UNIT 5 Caring for Clients With Medical-Surgical Crises UNIT 6 Caring for Clients With Respiratory Disorders UNIT 7 Caring for Clients With Cardiovascular Disorders UNIT 8 Caring for Clients With Hematopoietic and Lymphatic Disorders UNIT 9 Caring for Clients With Immune Disorders UNIT 10 Caring for Clients With Neurologic Disorders UNIT 11 Caring for Clients With Sensory Disorders UNIT 12 Caring for Clients With Gastrointestinal Disorders UNIT 13 Caring for Clients With Endocrine Problems UNIT 14 Caring for Clients With Breast and Reproductive Problems UNIT 15 Caring for Clients With Urinary and Renal Disorders UNIT 16 Caring for Clients With Musculoskeletal Disorders UNIT 17 Caring for Clients With Integumentary Disorders Appendix A: References and Suggested Readings Appendix B: Nursing Resources Appendix C: Commonly Used Abbreviations and Acronyms Appendix D: Laboratory Values Glossary
Includes bibliographical references (pages 1291-1320) and index
Keywords: Nursing; Surgical nursing